International campaign of solidarity with the People of Korea - Martinez (OSPAAAL (Organization of Solidarity with the People of Asia, Africa and Latin America), 1973)
Flag of North Korea on top; fallen bald eagle with streams of blood bursting from it at the bottom Poster in four languages advertising campaign of solidary with North Korea, June 25 - July 27 PO-1356